1982
DOI: 10.3402/tellusa.v34i6.10838
|View full text |Cite
|
Sign up to set email alerts
|

Available potential energy in the northern hemisphere during the FGGE year

Abstract: Northern Hemispheric twice daily data from the First GARP Global Experiment (FGGE) year are used to compare available potential energy estimates obtained using the so-called exact (isentropic) form of the equations with two commonly used approximate (isobaric) forms. The two approximate forms, one using a fixed lapse rate and the other a lapse rate which varies in the vertical, overestimate the total available potential energy except in mid-summer.The greatest difference between the exact and approximate forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The majority of studies have applied the latter system, owing to its reduced computational intensity and applicability to a traditional meteorological analysis, and for comparison to previous studies (e.g., Oort 1964;Muench 1965;Peixóto and Oort 1974;Wintels and Gyakum 2000;Pezza et al 2010). Studies comparing the exact and approximate equations have shown that the approximate equations generally overestimate the value of APE, but the temporal variability of APE is similar between the two frameworks (Dutton and Johnson 1967;Duck Min and Horn 1982). The terms of the Lorenz energy cycle can also be computed using spatial, temporal, or spatial and temporal averages, resulting in a spaceonly, time-only, and space-time analysis of the energetics terms (Oort 1964).…”
Section: B Energetics Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have applied the latter system, owing to its reduced computational intensity and applicability to a traditional meteorological analysis, and for comparison to previous studies (e.g., Oort 1964;Muench 1965;Peixóto and Oort 1974;Wintels and Gyakum 2000;Pezza et al 2010). Studies comparing the exact and approximate equations have shown that the approximate equations generally overestimate the value of APE, but the temporal variability of APE is similar between the two frameworks (Dutton and Johnson 1967;Duck Min and Horn 1982). The terms of the Lorenz energy cycle can also be computed using spatial, temporal, or spatial and temporal averages, resulting in a spaceonly, time-only, and space-time analysis of the energetics terms (Oort 1964).…”
Section: B Energetics Calculationsmentioning
confidence: 99%
“…Maximum values of A Z occur in winter months, decrease to a climatological minimum in summer, and increase in the fall months in association with the acceleration of the NH zonal jet (e.g., Peixóto and Oort 1974;Oort and Peixóto 1974;Cordeira 2011). Changes in static stability, though important, have a lesser impact on the budgets of A Z and A E (e.g., Dutton and Johnson 1967;Duck Min and Horn 1982). Subseasonal (10-50 day) variations in A Z account for a much smaller percentage (3.2%) of the total variability (Wintels and Gyakum 2000).…”
Section: Introductionmentioning
confidence: 99%